PENAFSIRAN AL-QURâ€™AN DENGAN FILSAFAT: TELAAH KITAB MAFÄ€TÄªá¸¤ AL-GHAYB FAKHRUDDÄªN AL-RÄ€ZÄª - Yuyun Zunairoh (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Qurâ€™anic exegesis has existed since the life of the Prophet Muhammad. It is divided into two forms, i.e. bi almaâ€™thÅ«rÂ and bi al-raâ€™y. Tafsir Falsafi is part of tafsir bil raâ€™y, which is built upon reasoning when interpretingÂ the Qurâ€™an. Some scholars reject this interpretation, but some accept it. Tafsir Falsafi is to interpret the Qurâ€™anby using philosophical approaches. Among the scholars are al-FarÄbÄ«, Ibn SÄ«nÄ, IkhwÄn al-á¹¢afÄ, and FakhruddÄ«nÂ al-RÄzÄ«. This paper will study FakhruddÄ«n al-RÄzÄ«, one of the most leading scholars in the subject, by focusingÂ on his great work the MafÄtÄ«á¸¥ al-Ghayb. This paper will examine a method of interpretation of al-RÄzÄ«, whichÂ is taá¸¥lÄ«lÄ«.Keywords: Tafsir Falsafi, MafÄtÄ«á¸¥ al-Ghayb, FakhruddÄ«n al-RÄzÄ«